Analisis Pengendalian Kualitas Produksi Kabinet Piano Jenis Side Arm R/L Model Up Polyester Dengan Menggunakan Metode PDCA - Siregar, M Tirtana; Munawar, Munawar; Cakranegara, Pandu Adi; Nurhuda, Hilmi Mufthia (Universitas Suryakancana, 2022)
This research aims to determine and analyze the quality control of the piano cabinet production type Side Arm R / L up polyester model in the Woodworking Department of the Cabinet Sides section of PT Yamaha Indonesia. The Side Arm R / L cabinet is the side part of the piano keyboard that serves to protect the piano keys so that they are stable when played. The problem occurs in product quality, especially on the Cabinet Side. In this study, the method used is the PDCA (Plan, Do, Check, Action) method with the Basic Seven Quality Tool as a tool. The PDCA method is used to solve the problem of the Cabinet Sides defect product. The data used in this final project is defect data for the Side Arm R / L cabinet during April 2019-March 2020. Based on the analysis, it is known that defects dominate 80% of the defects that occur, namely chipped, stretch (The results of the cabinet press are not meeting so that there is air going into the press). The main factors for the emergence of the three types of defects are the method, machine, and material aspects. Proposed improvements to address the causes of these defects include monitoring, recording, and evaluating errors in work methods and providing training for new operators and old operators who lack skills, schedule pre-operation inspections, and conduct assessment and maintenance of machines and tools work. As a result of the repair priority, the proportion of defects from May to June 2020 were all within the predetermined control limits, so it could be said that the process was under control.Â Penelitian ini bertujuan untuk mengetahui dan menganilisis pengendalian kualitas produksi kabinet piano jenis Side Arm R/L model up polyester pada Departemen Woodworking bagian Cabinet Side PT Yamaha Indonesia. Kabinet Side Arm R/L merupakan bagian sisi samping keyboard piano yang berfungsi untuk melindungi tuts keybord piano agar stabil ketika dimainkan. Permasalahan terjadi pada mutu produk, terutama pada bagian Cabinet Side. Dalam Penelitian ini metode yang digunakan adalah metode PDCA (Plan, Do, Check, Action) dengan alat bantu Basic Seven Quality Tool. Metode PDCA digunakan untuk menyelesaikan permasalahan defect product Cabinet Side. Data yang digunakan dalam Penelitian ini yaitu berupa data defect kabinet Side Arm R/L selama bulan April 2019-Maret 2020. Berdasarkan hasil analisis diketahui 80% defect yang terjadi didominasi oleh jenis defect yakni gompal, reggang, uki (Hasil pres kabinet tidak rapat sehingga ada udara masuk kedalam pres-presan). Faktor utama munculnya ketiga jenis defect tersebut adalah faktor metode, mesin, dan material. Usulan perbaikan untuk mengatasi penyebab terjadinya defect tersebut diantaranya adalah melakukan pengawasan, pencatatan, dan evaluasi kesalahan metode kerja yang digunakan serta memberikan pelatihan untuk operator baru dan operator lama yang kurang memiliki skill, membuat jadwal pemeriksaan pra-operasi dan melakukan pemeriksaan serta perawatan mesin dan alat kerja. Hasil dari prioritas perbaikan, proporsi defect selama bulan Mei sampai dengan bulan Juni 2020 seluruhnya berada dalam batas kendali yang telah ditetapkan, sehingga bisa dikatakan bahwa proses telahÂ terkendali.Â